DINAMIKA URBANISASI DI INDONESIA - Made Heny Urmila Dewi (PIRAMIDA, 2006)
Urbanization is a natural phenomenon in economic development process both in developed and less developed countries. Urbanization is not only viewed as a population phenomenon, but also viewed as political, social, cultural, and economic phenomenon. Data showed that the more developed the economic condition of a country, the higher the urbanization rate will be. One thing must be avoided related to urbanization is that high concentration of population in one region which caused agglomeration or primacy. Therefore, population controlling policy must be effective, integrated, and based on a policy that can harmonize social, economic, culture, political, and physical aspects.